Platformization and Dynamic Capabilities in the Digital Transformation of Legacy Media: A Case Study of PT Tempo Inti Media Tbk - Lizza Arnofia; anang sujoko; Reza Safitri (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2026)
Abstract. This study examines the multiplatform transformation of PT Tempo Inti Media Tbk as an Indonesian legacy media organization responding to digital disruption and the decline of print journalism. Background: The research is grounded in Dynamic Capabilities Theory, which explains how organizations sense opportunities, seize strategic directions, and transform internal structures, and Media Ecology Theory, which positions media change as an ecological shift affecting newsroom practices and audience behavior. These theories guide the study's primary objective: to analyze Tempo's adaptive strategies across technological, editorial, and business dimensions. Methods: This qualitative case study employs in-depth interviews with editors and digital managers, documentation of internal reports and platform analytics, and observational analysis of the integrated newsroom workflow. The primary outcomes measured include Tempo's platform integration, content production processes, and the implementation of communication strategies across digital channels. Results and Discussion: The findings show that Tempo undergoes three phases of transformation digitization, digitalization, and digital transformation supported by cross-platform content distribution, data-driven editorial decisions, and the restructuring of the newsroom into an integrated production system. Previous research on legacy media digital transformation aligns with these findings, particularly regarding the role of organizational agility and technological adoption. The theoretical connection reveals that Dynamic Capabilities shape Tempo's strategic decisions, while Media Ecology explains the broader communication shifts influencing platform adaptation. Conclusion: Tempo's transformation demonstrates how legacy media can develop strategic capabilities and communication practices to remain relevant and sustainable within a rapidly evolving digital ecosystem.   Keywords: communications theory; digital journalism; legacy media; media ecology; multiplatform transformation